Eastbound through Siberia : Observations from the Great Northern Expedition - Steller, Georg Wilhelm (Book collections on Project MUSE., 2020)
In the winter of 1739, Georg Steller received word from Empress Anna of Russia that he was to embark on a secret expedition to the far reaches of Siberia as a member of the Great Northern Expedition. While searching for economic possibilities and strategic advantages, Steller was to send back descriptions of everything he saw. The Empress's instructions were detailed, from requests for a preserved whale brain to observing the child-rearing customs of local peoples, and Steller met the task with dedication, bravery, and a good measure of humor. In the name of science, Steller and his comrades confronted horse-swallowing bogs, leaped across ice floes, and survived countless close calls in their exploration of an unforgiving environment. Not stopping at lists of fishes, birds, and mammals, Steller also details the villages and the lives of those living there, from vice-governors to prostitutes. His writings rail against government corruption and the misuse of power while describing with empathy the lives of the poor and forgotten, with special attention toward Native peoples. What emerges is a remarkable window into life'both human and animal'in 18th century Siberia. Due to the secret nature of the expedition, Steller's findings were hidden in Russian archives for centuries, but the near-daily entries he recorded on journeys from the town of Irkutsk to Kamchatka are presented here in English for the first time.